An Analysis of urban housing market and housing problem in Turkey - Sezener, Orhan (My University, 1987)
﻿ ﻿Özet 121 SOTMAir A1B @m&IMSBMS Housing which can be defined as a composite product resolving and reconciling all the diverse needs of its occupant differs from other commodities in many ways. First of all, it is both a capital good and a consumer product. It is bulky, immobile and fairly durable.lt requires heavy capital outlays in each production run. unlike, many other products, it is a heterogenous good. Its market represents a collection of sub-markets -which are composed of various income groups having different patterns of consumption. Fearfchermore, the market for housisg necessarily has local character because its product is fixed. la terms of demand, the most significant characteristic of housing is the difference between the need for housing and the demand for housing. f he demand for housing implies the amount of homsimg which the society can af f ord bfet the need. for housing; embraces the total requirement for shelter without consideration of wfeether or not families can pay for it. In a socie^r the need for housing is directly related to the 122 siz© of population and average family size.lhe demand, for housing, on the other hand, along with the size of population ana. average family, is determined by the levels and distribution of income ana prices of housing. !Ehe basic unit of: demand for housing is the family, fhe principal factors shaping a family * a demand for hqusing are family size and. household income »However, housing demand, of the family is als© affected Isj income expectations, cost and availability of financing, the distance of the dwelling to main employment areas, the quality of enviroment,and the cost and availability ©f public utilities in the neighborhood!. Housing supply, on the other side, is composed of existing housing stock and new housing construction. As it is difficult to acquire a higher level of housing supply in a short period of time due to the specific nature of housing, existing housing stock eompsoses a great proportion of housing supply. Since new housing construction makes marginal changes on housing stock every year, the ©efcivities of housing market often occur m thin the existing housing stoek.fhe aggregate supply of housing is related to the prices and quantities of land and. construction materials. In terms of supply, the most significant characteristic of housing is the high level of expenses Tihich should be repeated in each run of production. In the case of housing, as for other commodities, the market largely governs the quality, quantity, cost, price, and distribution of the product. Although there is usually a close relationship between prices of housing and costs of product! «pou price in housing market is a direct reflection of the interactions between demand andysupply.Eheoretically,a well- functioning market might be expected ta create ana maintain a 123 state of equilibrium which provides the sellers with cost, nıinimizatioa and profit maximization and the buyers mth utility maximization. However, the acfetel. functioning of the market falls short ©f this expectation because some imperfections which prevent the realization of perfect competition. Actually, perfect competition can not be realized in the ease of housing market because none of the basie assumptions of this model can be achieved. Firstly, housing; is not a homogenous commodity. Housing supply is very diverse in terms of size, quality, location, architectural type and design. Ivery unit of a country's housing stock may be suggested to be unique. likewise, the assumption of perfect knowledge of the sellers and buyers is missing in housing market because of the high cost of perfect knowledge. Si&ee the entire market for housing consists of a number of sub-markets and since it has local character due to the immobility of its commodity, for* a potential purchaser to explore the prices and equalities of all possible houses for sale at any time, even within a given area, involves him an impossibly large expenditure of time and money. Qfe the other side, a potential seller would also suffer if only chanoe could lead &$a&gmir to him. Furthermore, large volumes of capital outlays which have to be repeated in every production rum make the entry of new firms to the market quite difficult.For this reason, neither the assumption of freedom ©f entry nor the assumption of numerous telleo?® can be achieved in housing markets All of these factors prevent; the market for housing from reaching a competitive state and result in housing, defieit which is a common question of urban world, Developed and less developed countries, though they are worlds apart in wealth and technology, are both facing an urban housing problem. 124 problem is not particular to a few countries because entrepreneurs usually prom unable to shelter the population almost everywhere. Housing deficit gives rise to important economic and social problems. She deficit strongly influences the family budget because housing expend! tuiies are its second largest item.Housing deficit may alsa affect the success of economic policies of the governments adversely. fhe unsanitary and substandard living, conditions of squatters and slums,which are the results of Jhousing deficit, reduce the economic activity of their occupants. In addition, the s& settlements cause an increase in public expenditures. Squatters and slums, in general, lead to violence, increasing alienation, crime, air and water pollution. The main properties of these settlements are unemployment, poverty, venereal di©ease,high population m density and high rate of juvenile delinquency. As the deficit is inevitable due to the imperfections of housing market and as it opens way to> overwhelming econmic and social problems, government interference with the market is of vital importance. The main objective of government intervention is to> satisfy the housing requirements of the people. Howe ver, the methods of intervention might, differ according to the specific circumstances of the country. In Turkey, housing industry is very ijsp©:HWi£, Bousing occupies 80% of construction sector. The volume of employment of housing sector was estimated as 550.OOQ.The share of housing sector m&.s supposed to be 3.6# i® GHP and the share of housing investments in total investments was supposed to be 20% in the Bevel opment Plans. The existing housing stock in the country is estimated to be 4-5 million units including squatters -and other substandard dwellings. The existence of squatters, overcrowded, and substandard dwellings indicate the housing deficit, 125 Actually, housing deficit has been an important question for many decades in Turkey. There has always been a considerable difference between housing: supply and housing, need. T he inadequacy of annual housing supply in Turkey does not s%e® from tare insufficient level of resources allocated in this field.But it stems from some imperfections which are caused loj the sovereignty of private enterprise in housing sector. the adverse «f feet s created by the sovereignty of private enterprise meire accompanied by a set of additional factors such as high costs of urban land and construction materials, lopsided distribution of income, and high costs of credit. Consequently, the gap between housing production and housing need has reached to a striking si ze. Hie authorities gave emphasis to housing problem in the Bevelopment Plans and Gonsitutions.But until the early 1980» s a serious housing policy could not be observed. The first Mass Housing Code was put into- effect in 1981 but it could, not be: appliedi because of financial reasons. The second Mass Housing Code mas proclaimed in 1984» This law: aimM to stimulate the recovery in construction sector and promised, financial support to> lower and middle income groups. However, in a period of three years the code did. not reaeh to the predicted targets because it ignored, some of the causes of housing problem and it included some? imperfect ions. The activities of th© fundi eouldt not embrace the target income groups beoamse credit ratios were not determined realistically. Hevertheless,Mass Housing Code can be interpreted as the initial step of a comprehensive housing poliey.fhe authorities should, improve an,d apply some other policies i»hieh should be -synchronized, mth housing policy. These policies should offer 12& efficient solutions to> the problems which are related to housing. Housing p&licy should be accompanied by the policies which can reduce the inequality in distribution of income, increase the amount of urban land available for housing production, and decrease the high costs of construction materials. In sum, housing problem can not be solved with piecemal attempt s.îhe solution of the problem invokes a rational housing policy which is based on a broader setting and which is designed, as a part of a mder social ana economic policy..anyway, the eradication of housing deficit seems to require consistent approaches and considerable efforts.
Keywords: Ekonomi; Kentsel Konut Piyasası; Konut Sorunu_Türkiye